Evidence of austenite memory in PH 15-5 and assessment of its formation mechanism. (15th August 2019) - Brandl, Dominik; Lukas, Marina; Stockinger, Martin; Ploberger, Sarah; Ressel, Gerald
Abstract: Austenite memory and subsequent spontaneous recrystallization during austenitization is stated for some types of soft martensitic stainless steels such as X4CrNiMo16-5-1 or 13Cr5Ni but have not been proposed for the commercial alloy PH15-5 until now. However, the understanding of the austenitization behavior is defined to be crucial as it influences grain size, dislocation density of austenite and thus the final mechanical properties of the material. Therefore, this study investigates the austenitization behavior of PH15-5 by means of in-situ high temperature electron back scatter diffraction of continuous austenitization and directly evidences austenite memory also in this alloy. In order to characterize the austenite formation mechanism in detail, dilatometer, in-situ X-ray diffraction and confocal laser scanning microscope experiments have been carried out. Corroborated with thermokinetic DICTRA simulations, a diffusion controlled transformation exhibiting austenite memory is evidenced. The in-situ high temperature electron backscatter diffraction data in comparison with recent literature indicates the inheritance of geometrically necessary dislocations from martensite to austenite. Therefore, a basic model is postulated in order to describe the inheritance of geometrically necessary dislocations due to a diffusion controlled transformation process. Graphical abstract: Unlabelled Image Highlights: A diffusion controlled transformation from martensite to austenite is evidenced. Austenite memory is directly evidenced in PH 15-5. Inheritance of low angle grain boundaries from martensite to austenite is proposed.